Sainte-Bernardette du Banlay, Nevers - Christophe Joly; Orlane Brault; Paul Barnoud (In Situ)
The Sainte-Bernadette du Banlay church at Nevers was built from 1964 to 1965 to the designs of the architects Claude Parent and Paul Virilio, working on their theme of the oblique function. It was the fruit of an architectural competition organised in 1963 by Monseigneur Vial and the Abbé Bourgoin, the parish priest. The church’s architecture is inspired by that of defensive bunkers. Two reinforced concrete shells are joined the one into the other but out of true on a longitudinal axis. The overall appearance of the church is that of a monolithic block, something like a rock. Inside, two large oblique planes seem to emerge to create the nave and the chancel. Closely related to the Lourdes grotto of the Virgin’s appearances, the church is designed as a suspended crypt which adopts the shape of a heart in its cross section. By using untreated concrete and sky lighting, the architects succeeded in giving an astonishing intimacy to the church. There is a striking opposition between the austere exterior volume and the welcoming and protective space inside. The architects expressed a new function for the church in an age of uncertainty and tension.